How does green attitude, green advertising, and environmental awareness impact on green purchase intention? - Maharani, Tri Adinda; Shalahuddin, Ahmad; Listiana, Erna; Hasanudin, Hasanudin; Fauzan, Rizky (Enrichment : Journal of Management, 2023)
The world is now very concerned about how to maintain environmental balance, so there needs to be an urgent change in the way consumers pay attention to the importance of maintaining sustainability and environmental balance. Eco-friendly products are goods and services, including products that have applied the principles of preserving, protecting and managing the environment. Along with the development of technology, green advertising becomes one of the variables that is considered to determine the extent of its influence on the intention to green purchase products. Green advertising focuses on environmentally friendly advertising or marketing that aims to introduce environmentally friendly products to the public. This creates an audience attitude towards product evaluation. Using Analysis of Moment Structure (AMOS), this study tested the relationship among the variables that are independent and dependent with the presence of mediation variables. The method used in collecting data is to distribute questionnaires with a total of 206 respondents. Research conducted shows that green attitudes are positively impacted by green advertising. Environmental awareness also has a favourable effect on green attitudes. Additionally, environmental awareness and green advertising positively influence consumers' intentions to purchase ecologically friendly or green items. At the same time, the attitude mediates full green advertising and environmental awareness towards the purchase intention of green products.